Analysis on the productivity of maize hybrids in 2016 - Eduard Alexandru Dumitru; Ana-Ruxandra Micu; Dana Rebega (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The yield per hectare in agricultural products is influenced by many factors, from the type of soil, plants seed, the precipitates level, climate, culture technologies, and hybrid genetic potential of it is cultivated. So in the case of maize, these criteria can influence yields per hectare, which can cause redaction of farmer profitability. Currently on the market in Romania, farmers can choose from a wide range of hybrids, depending on the factors affecting the productivity of the farm.
Keywords: 330; hybrid; maize hybrids performance